2014
DOI: 10.1016/j.brainres.2014.05.024
|View full text |Cite
|
Sign up to set email alerts
|

The structure and function of actin cytoskeleton in mature glutamatergic dendritic spines

Abstract: Dendritic spines are actin-rich protrusions from the dendritic shaft, considered to be the locus where most synapses occur, as they receive the vast majority of excitatory connections in the central nervous system (CNS). Interestingly, hippocampal spines are plastic structures that contain a dense array of molecules involved in postsynaptic signaling and synaptic plasticity. Since changes in spine shape and size are correlated with the strength of excitatory synapses, spine morphology directly reflects spine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 127 publications
(121 reference statements)
0
53
0
Order By: Relevance
“…This is because dendritic spines have high concentrations of actin fibers at excitatory synapses, and actin affects the size and the synaptic strength of the dendritic spine [22][23]. Interestingly, recent studies have shown that Reelin alters the actin cytoskeleton dynamics through n-cofilin, which is important for dendiritc spine stability [24][25].…”
Section: Discussionmentioning
confidence: 97%
“…This is because dendritic spines have high concentrations of actin fibers at excitatory synapses, and actin affects the size and the synaptic strength of the dendritic spine [22][23]. Interestingly, recent studies have shown that Reelin alters the actin cytoskeleton dynamics through n-cofilin, which is important for dendiritc spine stability [24][25].…”
Section: Discussionmentioning
confidence: 97%
“…52 More broadly, abnormalities of size, density and shape of dendritic spines have been hypothesized to have a role in various brain disorders, including intellectual disability, 53 autism, 54 Alzheimer’s disease, 55 SCZ and BP, 56 as well as MDD. 57 There is also increasing evidence to suggest that they may additionally be involved in the regulation of mood: lowered spine densities have been found in postmortem brains with two prototypical mood disorders (BP and MDD) 56,57 ; in addition, chronic stress, long considered one of the most robust risk factors for mood disorders, has been associated with excessive pruning of dendritic spines; 58 and finally, the antidepressant ‘effect’ of both traditional and novel pharmacological agents has been proposed to be mediated by increased formation of dendritic spines in the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Gaining specificity by limiting the drug’s action to the cell type affected by AD is one approach to limiting the side effects of a new potential AD treatment. There are many neuron-specific signaling pathways that regulate cofilin phosphorylation levels, most of them mediated by proteins found localized at or near postsynaptic densities (Bellot et al, 2014; Spence and Soderling, 2015). Some of these pathways may be restricted to subsets of neurons in specific brain regions, such as the Pak3-mediated pathway involved in X-linked mental retardation (Allen et al, 1998).…”
Section: Challenges In Cellular Specificity Of Peptide Therapeuticsmentioning
confidence: 99%